Analysis of polydicyclopentadiene-metal hybrid adhesive joints for automotive exterior body applications - Camboa, André (2015)
An exterior body panel solution containing a polydicyclopentadiene skin attached to an interior metallic reinforcement through adhesive bonding is being studied to be applied in the MobiCar bonnet. With this solution is expected to achieve lightness, adequate structural integrity and cost-efficiency. However, there is uncertainty regarding to the bonnet adhesiveness since different metallic materials and adhesive types are being considered for its development. Thus, in this paper, several samples are tested through shear loading with the aim of understanding the loading magnitude expected by using polydicyclopentadiene, steel DC04+ZE and aluminum alloy AW5754-H111 as substrates adhesively bonded by an epoxy or a methacrylate. Methacrylate adhesive have shown greater shear strength in all types of adhesive joints. PDCPD joints presented the highest displacements. Surface degradation was considered adequate over abrading once none strength difference was seen between the different surface treatments. Steel treated by cataphoresis has shown the highest joint interface strength.